Energy efficiency assessment in the generator of an absorption heat transformer from measurement falling film thickness on helical coils. (15th December 2017) - Lazcano-Véliz, Y.; Hernández, J.A.; Juárez-Romero, D.; Bourouis, Mahmoud; Coronas, Alberto; Siqueiros, J.
Highlights: Optimal hole diameter of design in the distributor was determined. Operation flow in the generator was obtained. Experimental falling film thickness of LiBr/H2 O was measured. Convective heat transfer coefficient on the film side of LiBr/H2 O was calculated. Energy efficiency in the generator was estimated. Abstract: Heat exchange systems based on the falling film configuration need a detailed analysis of the design variables and operation of the distributor, which will ensure a homogeneous falling film pattern on a tube bank. The objective of this research was to determine the falling film thickness of the LiBr/H2 O at 55 wt%, as a function of the convective heat transfer coefficient on the film side. Different hole diameters and mass flow velocities were evaluated to analyze the falling film thickness behavior. The falling film analysis was carried out on a double concentric coil located in the generator ( GE ) of an absorption heat transformer ( AHT) coupled to a water purification system ( WP ). The falling film thickness was experimentally measured from the digital image processing technique. The fall pattern favored a homogeneous distribution falling film in dropwise form with which was obtained wetted efficiency values of 97% on the outer coil and 94% on the inner coil. From the definition of the design and operation variables in the distributor (hole diameter and mass flow velocity), some of the main variables that intervened in the heat transfer process were determined: the falling film thickness; the falling film average velocity; and the convective heat transfer coefficient on the film side. Under these operating conditions and design, the heat transfer efficiency values in the GE increased up to 95%. Consequently, the heat load was increased by 64% with respect to the original design of the helical bank of the GE .